PERHITUNGAN, PEMOTONGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 ATAS GAJI PEGAWAI TETAP PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG BANJARMASIN - mursyidah; Saipudin; Norlena (Universitas Lambung Mangkurat, 2025)
Implementation of Article 21 Income Tax on permanent employees’ salaries at KPKNL Banjarmasin, focusing on the use of the Average Effective Rate introduced in 2024. The research employed a qualitative and quantitative descriptive approach by reviewing payroll data, tax documentation, and interviews with relevant personnel. Findings reveal that TER simplifies monthly tax calculations, although a year-end adjustment using progressive rates may result in differences. Furthermore, the comparison between the office’s automated system and manual TER calculations showed slight discrepancies. Tax remittance is carried out via the SPM-LS mechanism, while reporting is submitted through the e-Bupot Government platform. Overall, tax compliance at KPKNL Banjarmasin aligns with current regulations, with minor technical aspects that could be further improved.